Szara strefa w gospodarce Ukrainy - Butyter, Daniel (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The share of shadow economy in Ukraine is very difficult to be evaluated, because nowadays it is a part of all sectors of social life. Solving problems related to shadow economy requires concerted efforts of the state in all areas of economic and social policy. One thing is certain, the real participation of shadow economy is far bigger than the one which appears in data of Ukrainian and foreign experts. The part of shadow economy is so huge, that macro- and micro-economical indicators do not reflect the real state of economy in Ukraine.The fact is that legal system of Ukraine, in its current state, cannot counteract the corruption and money laundering in Ukraine, which increases the share of shadow economy in Ukraine. The strategic priorities of legalizing Ukraine’s economy at present stage are stimulation of investment processes, improving monetary policy, creating favorable conditions for business development, significant reduction and equalization of the tax burden, simplifying tax system, strengthening tax control in terms of production costs, efficient management of the public sector of economy, increased state oversight of public funds, loans and foreign investment, counteracting laundering of proceeds from crime, etc.To improve the quality of the fight against corruption, the following steps should be taken: continuing the development of the judiciary, taking actions to improve the independence of the judiciary, considering the problem of performance of a number of government agencies that are designed to coordinate the fight against corruption, reviewing principles of financial support for law enforcement agencies and providing measures to improve their wages.For majority of the Ukrainians illegal work in the black market, graft, corruption have become a part of life, which makes the possibility of joining the European Community for Ukraine very doubtful, without radical changes in society.
Keywords: szara strefa; aktywność szarej strefy; stopa szarej strefy; Ukraina; korupcja